2018
DOI: 10.1002/uog.17550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human papilloma virus infection onin‐vitrofertilization outcome: systematic review and meta‐analysis

Abstract: Objectives To identify, appraise and summarize the available data concerning the impact of human papilloma virus (HPV) infection on reproductive outcome following in-vitro fertilization (IVF). Methods (RR, 0.43 (95% CI,; I 2 = 0%; three studies, 429 participants; P = 0.01) and miscarriage (RR, 3.70 (95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…Including all the relative publications concerning HPV and ART outcome, it was found that there is no enough evidence to draw solid conclusions regarding the impact of HPV infection in women on assisted reproductive outcomes. Further to the above founding, it was also reported that when HPV infection is present in the male partner, it appears that there is a negative effect on live birth/ongoing pregnancy rate and an increase in the miscarriage rate [ 51 ]. Lastly, following the previous novel meta-analysis, Xiong and colleagues [ 52 ], performed another meta-analysis relating the HPV risk with spontaneous abortion and spontaneous preterm birth (sPTB).…”
Section: Hpv and Assisted Reproductive Technology (Art)mentioning
confidence: 87%
See 1 more Smart Citation
“…Including all the relative publications concerning HPV and ART outcome, it was found that there is no enough evidence to draw solid conclusions regarding the impact of HPV infection in women on assisted reproductive outcomes. Further to the above founding, it was also reported that when HPV infection is present in the male partner, it appears that there is a negative effect on live birth/ongoing pregnancy rate and an increase in the miscarriage rate [ 51 ]. Lastly, following the previous novel meta-analysis, Xiong and colleagues [ 52 ], performed another meta-analysis relating the HPV risk with spontaneous abortion and spontaneous preterm birth (sPTB).…”
Section: Hpv and Assisted Reproductive Technology (Art)mentioning
confidence: 87%
“…A recent novel meta-analysis performed by Siristatidis and colleagues [ 51 ] is the first one that complexes the HPV infection and ART outcome. Including all the relative publications concerning HPV and ART outcome, it was found that there is no enough evidence to draw solid conclusions regarding the impact of HPV infection in women on assisted reproductive outcomes.…”
Section: Hpv and Assisted Reproductive Technology (Art)mentioning
confidence: 99%
“…Although previous meta-analyses have established an association between HPV infection and both male infertility (Lyu et al, 2017) and the outcomes of natural or IVF/ICSI pregnancies (Siristatidis et al, 2018;Xiong et al, 2018), little is known regarding its role in female infertility. This is thought to be the first meta-analysis of studies comparing the prevalence of HPV infection in the infertile and general female population.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al (2018) found that infection with the indiscriminate HPV genotype increased the risk of spontaneous abortion, and HR-HPV infection was a risk factor for spontaneous preterm birth. However, there is not enough evidence to indicate an association between HPV infections and the pregnancy or spontaneous abortion rates of ART (Siristatidis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Though studies have established an association between HPV infection and both male infertility [24][25][26][27] and assisted reproductive technology (ART) outcomes [28][29][30], the mechanism by which HPV infection decreases female fertility remains unclear. However, Yuan et al performed a meta-analysis on HPV infection and female infertility which showed a significant association between HR-HPV and female infertility (odds ratio 2.33, 95% CI 1.42-3.83, p = 0.0008) but surmised that HR-HPV is more likely a trigger factor rather than an independent cause [31].…”
Section: Discussionmentioning
confidence: 99%